Psychological Stress Among A Sample of Orphans in Aqaba Governorate and its Relationship With Psychological Hardiness and Life Quality Among Them - Alnaimat, Mahmoud Haroun; Arabiat, Ahmad Abdel-Haleem (Journal of Educational and Psychological Sciences, 2021)
The study aimed to identify the psychological stress level among orphans in Aqaba governorate and its relationship with both psychological hardness and life quality. The sample of the study was consisted of ( 102 ) male and female Orphans students whom were selected using the simple random method of sample selecting. Three scales were developed: The Psychological Stress Scale, The Psychological Hardiness Scale and The Life Quality Scale, these scales were checked for reliability and consistency, results indicated that the psychological stress level among orphan students in Aqaba governorate was medium as the emotional dimension came first with a high level while the physiological dimension came second with a medium level. Results also indicated a significant statistical negative relationship at α≥ 0.05 between psychological stress and its dimensions from the one hand, and each of psychological hardiness with its dimensions and life quality with its dimensions in the other. In addition, results indicated no differences between the two genders in the psychological stress level as whole and it was cognitive and emotional dimensions, but indicated differences between male and female participants in the physiological dimension for psychological stress. Finally, the study included a number of recommendations including: further studies dealing with the relationship of psychological stress and other variables, the orphans of self-esteem and psychological adjustment.